A Fatal Case of Isolated Methiopropamine (1-(Thiophen-2-yl)-2-Methylaminopropane) Toxicity. (September 2015) - Anne, Sravan; Tse, Rexson; Cala, Allan David
<x xml:space="preserve">Abstract</x> Abstract Methiopropamine (1-(thiophen-2-yl)-2-methylaminopropane) is a synthetic methamphetamine analogue and is classified as a novel psychoactive substance. The use of novel psychoactive substance has been increasing substantially for recreational purpose in recent years. Methiopropamine was first detected in 2011 in Finland and was later detected in the United Kingdom. It can be purchased on the Internet and is currently poorly regulated. Reported adverse effects of methiopropamine use are mostly anecdotal user reports on Internet forums, and there are limited data on its pharmacodynamics and toxicity in the literature. Death as a direct result from methiopropamine toxicity has not been reported in Australia. We report here the first case of death caused by recreational use of methiopropamine in Australia. This same incident highlights the first ever death from isolated methiopropamine use. Being an analogue of methamphetamine, we hypothesize that the mechanism of death caused by methiopropamine would not be dissimilar to methamphetamine.